PEMBUATAN MEDIA PEMBELAJARAN BACA TULIS HITUNG (CALISTUNG) BAGI MASYARAKAT DI DISTRIK ULILIN - Andi Saparuddin Nur Andi; Tobias Nggaruaka; Agus Kichi Hermansyah (Bahasa Indonesia, 2019)
Abstract The ability of Calistung is a basic knowledge that must be possessed by someone to be able to learn various things. Merauke Regency still has lliteracy problems related to the low ability of Calistung, especially in Baidub Village, Ulilin District. The purpose of this service is to provide training and assistance to the community in Kampung Baidub to be able to improve the ability of Calistung. Service methods used are through the stages of observation, socialization, mentoring training, monitoring and evaluation. The activity will take place in May-August 2019 with the target of the illiterate community and students of Bupul XII Elementary Inpres in Baidub Village, Ulilin District. The results of this dedication were obtained by Calistung learning media in the form of simple counting tools (abacus), picture cards, word boards, and Calistung books. The level of community participation and students participating in the activities is very high as indicated by the ability of the community Calistung and elementary students in Baidub Village to increase after the implementation of the service. Abstrak Kemampuan Calistung merupakan pengetahuan dasar yang harus dimiliki oleh seseorang untuk dapat mempelajari berbagai hal. Kabupaten Merauke masih memiliki permasalahan penuntasan buta aksara terkait rendahnya kemampuan Calistung khususnya di Kampung Baidub, Distrik Ulilin. Tujuan dilaksanakannya pengabdian ini adalah untuk memberikan pelatihan dan pendampingan kepada masyarakat di Kampung Baidub agar mampu meningkatkan kemampuan Calistung. Metode pengabdian yang digunakan melalui tahapan observasi, sosialisasi, pelatihan pendampingan, monitoring dan evaluasi. Pelaksanaan kegiatan berlangsung pada Bulan Mei-Agustus 2019 dengan sasaran masyarakat buta aksara dan siswa SD Inpres Bupul XII di Kampung Baidub, Distrik Ulilin. Hasil pengabdian ini diperoleh media pembelajaran calistung berupa alat hitung sederhana (sempoa), kartu bergambar, papan kata, dan buku Calistung. Tingkat partsisipasi masyarakat dan siswa mengikuti kegiatan tergolong sangat tinggi yang ditunjukkan dengan kemampuan Calistung masyarakat dan siswa SD di Kampung Baidub mengalami peningkatan setelah pelaksanaan pengabdian.